Structural Health Monitoring of Timber Using Electromechanical Impedance (EMI) Technique. (8th July 2020) - Han, Fang; Zhang, Quanjing; Wang, Chengfeng; Lu, Guangtao; Jiang, Jinwei
Abstract : Nowadays, the electromechanical impedance method has been widely used in the field of structural healthy monitoring, especially for the concrete and steel materials. However, the electromechanical impedance studies on damage detection for timber are limited due to the anisotropic and ununiform biomaterial properties. As a low-cost and environment-friendly building material, timber has been widely used in the construction. Thus, it is beneficial to develop electromechanical impedance technique for structural healthy monitoring of timber so as to ensure the stability and safety of the entire timber structures. In this paper, two damage factors, i.e., the damage location factor and the damage size factor of timber specimens are investigated by using the electromechanical impedance method. The method is implemented by using a patch of Lead Zirconate Titanate transducer both as an actuator to generate stress waves and a sensor to detect stress waves after propagating across the timber specimens. Then, the damage index-root mean square deviation is employed to evaluate the damage severity of the timber specimens. The results indicate that the damage index changes consistently with the change of damage location and size factors, and the proposed method using electromechanical impedance technique can efficiently estimate the damage and its severity.